Biogeochemical interactions between aged cementitious materials and sulfate reducing microbial community with propionate as electron donor in the context of nuclear waste repository. (May 2023) - Durban, Nadège; Bertron, Alexandra; Sonois-Mazars, Vanessa; Schiettekatte, Maud; Matar, Gerald; Albina, Pierre; Albrecht, Achim; Robinet, Jean-Charles; Erable, Benjamin
Abstract: Heterotrophic microbial sulfate reduction can occur in both natural and engineered systems. The process can influence the radionuclide speciation and mobility in deep repository of radioactive waste (DRRW). DRRW are characterised by significant masses of concrete, imposing alkaline pH in the waste cell. This paper aims to evaluate microbial sulfate reduction coupled with propionate oxidation influenced by the alkalinity of the environment: moderate alkaline pH close to 9.0 without cement paste, and moderate alkaline pH which was then moderately increased (pH 9.0 to 9.4) by the presence of pre-aged solid cement pastes via advanced and moderate ageing protocols, respectively. Regardless of the degree of ageing of the cement pastes, the sulfate reduction rate decreased by up to 84% when the pH increased from 9.0 to 9.4 in the presence of cement paste and by up to 90% in the absence of cement paste. No sulfate reduction or propionate oxidation was observed for pH > 9.5. Microbial metabolites, sulfide, CO2 and acetate, produced from the reduction of sulfate and oxidation of propionate, and the presence of the microorganisms attached to the cement pastes (composed of up to 80% of sulfate reducing bacteria) led to their biodeterioration. Sulfide enrichment, precipitation of secondary ettringite, and intensified decalcification were notably detected. Self-healing like phenomena were also observed: calcium leached from the cementitious phases reacted with carbonate produced by microorganisms to form of calcium carbonate relocated either in the micro-cracks or on the surface of the pre-aged solid cement pastes. Highlights: Propionate is used as electron donor for biological sulfate reduction in cementitious environment. Biological sulfate reduction is strongly affected by pH increase especially for pH > 9.3 Microorganisms attached to the cement paste surface. Decalcification of solid cement paste is favored by microbial activity. Calcium from cement recombined as calcite in microcracks and on the solid surface.